Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s10620-013-3001-6
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibition Prevents the Formation and Promotes the Healing of Indomethacin-Induced Intestinal Ulcers in Rats

Abstract: Backgrounds & Aims We studied the intestinotrophic hormone glucagon-like peptide-2 (GLP-2) as a possible therapy for non-steroidal anti-inflammatory drug (NSAID)-induced intestinal ulcers. Luminal nutrients release endogenous GLP-2 from enteroendocrine L cells. Since GLP-2 is degraded by dipeptidyl peptidase IV (DPPIV), we hypothesized that DPPIV inhibition combined with luminal administration of nutrients potentiates the effects of endogenous GLP-2 on intestinal injury. Methods Intestinal injury was induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 56 publications
3
30
0
Order By: Relevance
“…The GLP-2 (3-33) form lacks in vivo activity [41,42]; however it can weakly activate the GLP-2 receptor (GLP-2R) when administered at supraphysiological doses [43]. Because of GLP-2's short (approximately 7-min) half-life in humans [44], administration of DPP-IV inhibitors has been used to enhance the therapeutic effects of GLP-2 [45][46][47], and synthetic GLP-2 analogs that are resistant to DPP-IV degradation have been used to prolong and increase its biological activity. Modifications include replacing the Ala (2) residue with Gly [40,42], which increases the half-life of GLP-2 to approximately 3 h in humans [48], or conjugating the peptide to various polymers, which extends the half-life in humans to as great as 10 d, based on theoretical projections from animal models [49][50][51].…”
Section: Glp-2 Synthesis and Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…The GLP-2 (3-33) form lacks in vivo activity [41,42]; however it can weakly activate the GLP-2 receptor (GLP-2R) when administered at supraphysiological doses [43]. Because of GLP-2's short (approximately 7-min) half-life in humans [44], administration of DPP-IV inhibitors has been used to enhance the therapeutic effects of GLP-2 [45][46][47], and synthetic GLP-2 analogs that are resistant to DPP-IV degradation have been used to prolong and increase its biological activity. Modifications include replacing the Ala (2) residue with Gly [40,42], which increases the half-life of GLP-2 to approximately 3 h in humans [48], or conjugating the peptide to various polymers, which extends the half-life in humans to as great as 10 d, based on theoretical projections from animal models [49][50][51].…”
Section: Glp-2 Synthesis and Degradationmentioning
confidence: 99%
“…Of interest, taste receptor T1R1-T1R3 activation by both L-glutamate and inosine 5 0 -monophosphate increases GLP-2 release in rat duodenum [100], and both GLP-2 administration and a combined treatment of L-alanine with inosine 5 0 -monophosphate increase the healing rate of intestinal ulcers in rats [47]. In addition, Bauchart-Thevret et al [101] demonstrated that dietary monosodium glutamate supplementation of preterm pigs dose-dependently increases plasma GLP-2 concentration.…”
Section: Potential Uses Of Glp-2 and Stimulators Of Glp-2 Secretion Imentioning
confidence: 99%
“…Since DPP-4 rapidly degrades and deactivates GLP-2, DPP-4 inhibitors are viewed as a novel method for treating of intestinal inflammation (15,16). It has previously been shown that DPP-4 inhibitors have a protective effect on indomethacin-induced intestinal damage in rats (17,18). However, in terms of colon carcinogenesis, exogenous and endogenous GLP-2 has been identified as a factor that increases colon carcinogenesis in azoxymethane-treated mice (19).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent preliminary trial by another researcher have shown some efficacy of lubiprostone (a bicyclic fatty acid derived from PGE1) [35], mesalazine (treatment of inflammatory bowel disease) [36] and dipeptidyl peptidase IV (treatment of diabetes mellitus) [37] for treatment of NSAID-induced injuries in experimental models, and further study will be needed.…”
Section: Current Strategy For Nsaid-induced Small Intestinal Injuriesmentioning
confidence: 99%